Amazing Digital Women Entrepreneurs Theory and The Impact of Artificial Intelligence on Beauty Industry - Saurav Kumar (Jurnal Ekonomi Bisnis Digital, 2026)
"Amazing digital women entrepreneur’s theory" was developed by Saurav Kumar. This theory states that digitalization is not an escape way for women entrepreneurs in prominent economic nations from the glass ceiling effect; rather, it is their capability to adopt digitalization more efficiently in comparison to their counterparts, the men. The term "Amazing digital women entrepreneurs" was coined by Saurav Kumar. Worldwide, women as homemakers stand out as the most suited reference of a complete managerial profile, handling purchases, appointments, budget control, and stock inventory with hardly any faults. However, for decades there has not been a prominent number evidencing their contribution as entrepreneurs in the world economy. This condition is changing, with a rise in their numbers in the digitalization age, as digital technology has empowered them to overcome barriers often called the glass ceiling effect. Digitalization is rapidly reshaping business operations by creating new avenues for growth and innovation. Some researchers pose digitalization as an escape way for women entrepreneurs to avoid obstacles, while others argue otherwise. This paper argues whether digitalization serves as an escape way for women entrepreneurs from the glass ceiling effect or reflects their capability to adopt digitalization more efficiently than men, and also examines the impact of artificial intelligence on the beauty industry. This research identifies reasons for the growth of women entrepreneurs in prominent economic nations during the digitalization age by studying them through four leadership theories, while also examining AI's impact on the beauty industry. Evidence confirms the existence of women entrepreneurs across transformative, servant, skill, and situational leadership theories. Additionally, beauty tech, by capitalizing on AI and big data, is becoming a powerful tool for brands to meet consumer expectations while boosting competitiveness in a crowded market.